Maceral composition, coal characteristics and depositional environment of the Middle Jurassic Nariinsukhait coal deposit, Southern Mongolia - Norov Baigalmaa; Bat-Orshikh Erdenetsogt; Luvsanchultem Jargal; Avirmed Baatarkhuyag; Damba Altantsetseg (Mongolian Geoscientist, 2024)
The Nariinsukhait deposit is the largest Jurassic coal deposit in southern Mongolia. A total of 90 core samples were obtained from a 493.1 m deep borehole in the central part of the deposit and tested for proximate analysis and caking properties, while 29 composite samples were analyzed for maceral composition and random vitrinite reflectance. The thick seam V stands out for its better quality compared to the upper seams, with an average ash content of 12.4% (ad), total sulfur of 0.5% (ad), volatile matter of 36.7% (daf), inherent moisture of 0.6% (ad), calorific value of 6,600 kcal/kg (ar), and a G index of 84 (ad). Seam V is characterized by higher inertinite content (32.2 vol.%), and lower vitrinite (58.0 vol.%) and mineral matter contents (6.7 vol.%) relative to the upper seams. Additionally, this seam has a higher rank, with random vitrinite reflectance (Rrand) of 0.77%, compared to 0.65-0.70% for the upper seams. According to MNS 6457:2023 standards, seam V is classified as “1/3 coking coal”, while the upper seams are classified as “high volatile gas coal”. Based on TPI, GI and A/I indices, seam V was deposited in oxic, ombrotrophic mire, whereas the upper seams were formed in mesotrophic and rheotrophic mires with high water tables and less oxic conditions. Due to these depositional environments, seam V exhibits higher inertinite, lower ash, and lower sulfur contents than the upper seams. The rank of the Nariinsukhait coals is comparable to that of Jurassic coals in central Mongolia, while the maceral composition and coal quality of the upper seams align with those of Jurassic coals. Seam V is distinct in its high inertinite and low total sulfur contents. The Nariinsukhait coal is primarily semi-soft coking coal (2/3 of total coal resources) and is also suitable as high-quality PCI coal. Further detailed studies are recommended to evaluate its potential for liquefaction and as a coking coal blend.